Identifikasi Miskonsepsi Materi Kinetika Kimia Pada Mahasiswa Tahun Kedua Pendidikan Kimia Teachers College - Purba, Friska Juliana; Sihombing, Chatrina Yohana; Inabuy, Marchella (UNIB Press, 2025)
The student’s learning outcome on 1st general chemistry is in the low score. Based on the observation, most of the students tend to memorize the formulas rather than understand the concepts that involve in almost chemistry subjects. Sometimes, this could lead to a misconception. Through this research, we are trying to identify the misconception that commonly happen in Chemical Kinetics to avoid the protracted mistakes that might affect the profession of theses student-teacher candidates. From this finding, it will also help the lecturers to find better teaching strategies and methods. The research approach used is a qualitative and descriptive approach. Subject of this research is the seconds year student-teacher candidates of chemistry education in Teachers College. The instrument that help to gather the student’s misconceptions is a four-tier diagnostic questions test, and to get more information on what causing the misconceptions we will do interview to some of the students. From the analysis there are 52.17% of student who are misconception in rate equation reaction, 30.43% in order reaction, 13.04% inactivation energy, 17.39% rate constant reaction. From the inteview, it was found out that the causes of misconceptions are such as students’ unreadiness, inaccuracy in applying the concept during the learning process and lack of practices.